2007
DOI: 10.1097/qad.0b013e3282ba553a
|View full text |Cite
|
Sign up to set email alerts
|

African infants' CCL3 gene copies influence perinatal HIV transmission in the absence of maternal nevirapine

Abstract: We observed a strong association between higher infant CCL3L1 gene copies and reduced susceptibility to HIV in the absence of maternal nevirapine. We also observed a reduction in newborn CCL3 production with nevirapine exposure. Taken together, we hypothesize that nevirapine may have direct or indirect effects that partly modify the role of the CCR5 ligand CCL3 in HIV transmission, obscuring the relationship between this genetic marker and perinatal HIV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 23 publications
4
53
0
Order By: Relevance
“…[1][2][3][4] It is to be noted that there seems to be an enrichment of CNV in immune response genes 1 such that they may contribute to the observed inter-individual variability in susceptibility to infectious diseases, vasculitis and autoimmune diseases. For example, we and others found that the copy number of segmental duplication on chromosome 17q that contains the gene encoding the chemokine CC chemokine ligand 3-like 1 (CCL3L1) influences HIV-AIDS susceptibility, [5][6][7][8][9] and the risk of developing Kawasaki's disease, 10 systemic lupus erythematosus (SLE) 11 and rheumatoid arthritis (RA). 12 CNV in the gene encoding the complement component C4 and FCGR2C has been associated with SLE 13 and idiopathic thrombocytopenic purpura, 14 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It is to be noted that there seems to be an enrichment of CNV in immune response genes 1 such that they may contribute to the observed inter-individual variability in susceptibility to infectious diseases, vasculitis and autoimmune diseases. For example, we and others found that the copy number of segmental duplication on chromosome 17q that contains the gene encoding the chemokine CC chemokine ligand 3-like 1 (CCL3L1) influences HIV-AIDS susceptibility, [5][6][7][8][9] and the risk of developing Kawasaki's disease, 10 systemic lupus erythematosus (SLE) 11 and rheumatoid arthritis (RA). 12 CNV in the gene encoding the complement component C4 and FCGR2C has been associated with SLE 13 and idiopathic thrombocytopenic purpura, 14 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies of varying size performed to evaluate the association between the CCL3L1 copy number and HIV-1/AIDS susceptibility (Gonzalez et al, 2005;Kuhn et al, 2007;Nakajima et al, 2007;Shao et al, 2007). The main features and outcomes of these studies are summarized in Table 1 .…”
Section: Cnv In Ccl3l1 and Susceptibility To Hiv-1/aidsmentioning
confidence: 99%
“…These results suggested that further analyses are required to clarify the association of the CCL3L1 copy number with HIV-1/AIDS susceptibility. Kuhn et al (2007) investigated whether the maternal or infant CCL3L1 copy number is associated with perinatal HIV-1 transmission and compared the CCL3L1 copy number between HIV-1 transmitting and non-transmitting motherinfant pairs. Infant, but not maternal, CCL3L1 copy number was found to be a determinant of enhanced perinatal HIV-1 transmission.…”
Section: Cnv In Ccl3l1 and Susceptibility To Hiv-1/aidsmentioning
confidence: 99%
“…As in adults, a single or a few founder variants are typically transmitted (Hahn et al, 2003;Renjifo et al, 2003;Verhofstede et al, 2003;Ramakrishnan et al, 2005Ramakrishnan et al, , 2006Gray et al, 2007a;Kourtis et al, 2011;Mabuka et al, 2013). Fetal or neonatal gene polymorphisms in IL-1, stromal cell-derived factor 1, Toll-like receptor 9, CCR5 (the HIV coreceptor), CCL3L1 (the ligand for CCR5), the Fc receptor γRIIA, CCR2 (a receptor that mediates the migration of monocytes to tissues), and the HLA alleles class I and II of the mother and of the fetus also affect perinatal transmission of HIV (Brouwer et al, 2004(Brouwer et al, , 2005Pillay and Phillips, 2005;De Souza et al, 2006;Kuhn et al, 2007;Ricci et al, 2010;Gianesin et al, 2012;Ahir et al, 2013). Several obstetrical events and practices, such as the duration of membrane rupture and cesarean section, increase or decrease HIV transmission, respectively (Cotter et al, 2012;Briand et al, 2013).…”
Section: Maternal To Child Transmissionmentioning
confidence: 97%